2010
DOI: 10.5487/tr.2010.26.2.157
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Characteristics of Atmospheric Heavy Metals in Subway Station

Abstract: In this study, we investigated the atmospheric heavy metal concentrations in the particulate matter inside the subway stations of Seoul. In particular, we examined the correlation between the heavy metals and studied the effect of the heavy metals on cell proliferation. In six selected subway stations in Seoul, particulate matter was captured at the platforms and 11 types of heavy metals were analyzed. The results showed that the mean concentration of iron was the highest out of the heavy metals in particulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…This is consistent with reports indicating that the air in busy train stations contains large amounts of copper generated by overhead train wire supplying electrical power (Kim et al. ; Loxham et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with reports indicating that the air in busy train stations contains large amounts of copper generated by overhead train wire supplying electrical power (Kim et al. ; Loxham et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Iron in particular is regarded as characteristic of the particulate matter found in underground systems [ 10 , 13 , 31 ]; in such environments, iron-containing particles are chiefly generated by mechanical wear and tear and friction at the wheel-rail and wheel-brake interfaces and between the pantograph and the overhead cables. These processes initially produce particles of metallic iron, which, on reacting with the oxygen present in the air, are transformed into iron oxide.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the level of the seven heavy metals, they were compared to levels of heavy metals in a previous study conducted in Seoul, South Korea 14 . The results showed that the mean Fe level was the highest of the heavy metals in PM, followed by Zn, Ni, Mn, Cr, respectively 14 .…”
Section: Discussionmentioning
confidence: 99%